2016
DOI: 10.1111/papr.12478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Percutaneous Octapolar Leads in Pain Treatment with Spinal Cord Stimulation of Patients with Failed Back Surgery Syndrome During a 1‐Year Follow‐Up: A Prospective Multicenter International Study

Abstract: Use of percutaneous octapolar SCS leads gives significant long-term pain relief and improvement in quality of life and sleep in FBSS patients. The outcomes are better than reported on 4-contact leads and indicate that the progress in SCS technology that has taken place during the past decade correlates with therapy improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…These rates are similar to those reported in other registries (Gatzinsky et al., ; Rosenberg et al., ), although the follow‐up in this study was longer (2 years vs. 1 year). Multi‐focal pain was also treated, and pain reduction of ≥50% was reported for primo‐implant patients with non‐predominant pain in lower limbs, back and upper limbs, with responder rates of 56%, 44% and 75% at 2 years, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These rates are similar to those reported in other registries (Gatzinsky et al., ; Rosenberg et al., ), although the follow‐up in this study was longer (2 years vs. 1 year). Multi‐focal pain was also treated, and pain reduction of ≥50% was reported for primo‐implant patients with non‐predominant pain in lower limbs, back and upper limbs, with responder rates of 56%, 44% and 75% at 2 years, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This observational study aimed to assess the effectiveness of SCS therapy and collect long‐term safety information in patients with chronic refractory lower limb, back or upper limb pain from a representative sample of implanting sites in France. Patient demographics were very similar to those reported in the literature in terms of age and pain location (Gatzinsky et al., ; Kumar et al., ; Rosenberg et al., ). The median pain duration of 3.5 years at study entry for patients in the primo‐implant group was shorter than the 10 years reported in the multicentre, observational EMP3OWER ™ study (Rosenberg et al., ), but comparable with the “time since last surgery” reported in the PROCESS trial (Kumar et al., ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“… 14) SCS was more efficacy for lower extremity or lumbar pain. 17 , 31) In our study, rates of long-term effects were 100% (3/3) of facial pain and 66.7% (2/3) of upper extremity pain in MCS, and 66.7% (6/9) of lower extremity pain and 75% (3/4) of both lower extremity and lumbar pain in SCS. However, there were no statistical difference between site of pain and efficacy of MCS/SCS.…”
Section: Discussionsupporting
confidence: 46%
“… 29 , 30) Percentages found for long-term effects in patients who have been subjected to more than 12 months of FBSS and CRPS type I were reported to be 60–70% and 63–72%, respectively. 17 , 31 , 32) In our current series, the total rate for the long-term effect of SCS was 57.1%, with this rate affected by the proportion of the number of FBSS and CRPS type I in the patient groups. In our study, 23% of the total patients were FBSS and CRPS type I, while 63% had central neuropathic pain.…”
Section: Discussionmentioning
confidence: 46%